Determination of effective factors in breastfeeding duration using survival analysis - RezaAli Mohamadpour; Nasser Behnampour; fateme abdollahi; AmeneSadat Sheykholeslami; Zahra Mehrbakhsh; Somaie Barzanuni (Golestan University of Medical Sciences, 2017)
Background: Breast milk is the most suitable nutrition for the neonates. Breast milk and breastfeeding duration can contribute to decreased mortality rate, intestinal bleeding, and various neonatal diseases (e.g., digestive and respiratory diseases). It can also reduce the risk of diabetes and obesity in childhood and adulthood. Therefore, the estimation of breastfeeding duration and recognition of the effective factors in this regard can lead to designing and implementing appropriate programs, which can provide the foundations for the modification of breastfeeding behavior. Methods: This survival study was conducted on 501 mothers with healthy and single birth neonates born within March 21, 2011-September 21, 2012 with active medical records in Aqqala city, Golestan province, Iran, in the second half of 2014. The data were collected from the information registered at the archives of health centers by in-person visiting. In addition, some of the information was collected through phone contacts. The duration of breastfeeding was estimated in month. Data analysis was carried out using the Cox regression in the STATA software, version 11.  Results: According to the results, the mean and median of breastfeeding were 20.44 and 22 months, respectively. According to the Cox regression, maternal ethnicity, living with family, birth spacing, type of milk consumed along with complementary nutrition, and type of neonatal nutrition during the hospital stay of the infant had a significant relationship with the early cessation of breastfeeding. Conclusion: Based on the findings of the present study and the identified factors affecting the breastfeeding duration, it seems necessary to provide the essential trainings for the young mothers and pregnant women to avoid of reducing the duration   of breastfeeding. These educations can be included in the programs of the Health centers of the universities and urban and rural medical clinics.